Implication of O2 dynamics for both N2O and CH4 emissions from soil during biological soil disinfestation - Chen Wang (Nature Portfolio, 2021)
Abstract Soil O2 dynamics have significant influences on greenhouse gas emissions during soil management practice. In this study, we deployed O2-specific planar optodes to visualize spatiotemporal distribution of O2 in soils treated with biological soil disinfestation (BSD). This study aimed to reveal the role of anoxia development on emissions of N2O and CH4 from soil amended with crop residues during BSD period. The incorporation of crop residues includes wheat straw only, wheat straw with biochar and early straw incorporation. The anoxia in soil developed very fast within 3 days, while the O2 in headspace decreased much slower and it became anaerobic after 5 days, which was significantly affected by straw and biochar additions. The N2O emissions were positively correlated with soil hypoxic fraction. The CH4 emissions were not significant until the anoxia dominated in both soil and headspace. The co-application of biochar with straw delayed the anoxia development and extended the hypoxic area in soil, resulting in lower emissions of N2O and CH4. Those results highlight that the soil O2 dynamic was the key variable triggering the N2O and CH4 productions. Therefore, detailed information of soil O2 availability could be highly beneficial for optimizing the strategies of organic amendments incorporation in the BSD technique.